ANALYSIS OF JUDGES' DECISIONS ON CRIMINAL SANCTIONS FOR ILLEGAL FISHING RECIDIVISTS: (Study of Sinabang District Court Decision Number 7/Pid.Sus/2022/PN Snb jo 28/Pid.Sus/2016/PN Snb) - Widya Safira; Ilka Sandela (Transpublika Publisher, 2023)
This research aims to analyze the considerations and reasons of judges when determining the same punishment for recidivist offenders engaged in illegal fishing, as well as the factors that contribute to the ineffectiveness of sanctions imposed on illegal fishing perpetrators. Recidivism is regulated in Articles 486, 487, and 488 of the Criminal Code, which stipulate that the penalty for repeat offenses should be increased by 1/3 of the previous sentence. However, in decision number 7/Pid.Sus/2022/PN Snb jo 28/Pid.Sus/2016/PN Snb, the judge imposed the same sentence of 3 years in prison for the defendant, without increasing the sentence as required. The research utilizes normative juridical and empirical juridical methods. The findings indicate that, in determining sanctions, judges consider aggravating and mitigating circumstances for the defendant. Their decisions are not solely based on formal evidence, but also rely on the judge's conviction. The judge's reasoning for imposing the same sanctions in this case was due to the fact that the defendant did not own the object of the crime, demonstrated good behavior during the trial, and was the breadwinner of the family. Factors contributing to the ineffectiveness of the imposed sanctions include lenient penalties, factors related to law enforcement, environmental considerations, and socio-economic factors.